Framed - Cottrell Boyce, Frank (McCmillan, 2005)
Dylan and his sisters have some ideas about how to make Snowdonia Oasis Auto Marvel into a more profitable business, but it is not until some strange men arrive in their small town of Manod, Wales with valuable paintings, and their father disappears, that they consider turning to crime.